PENGARUH PERAWATAN METODE KANGURU TERHADAP PENINGKATAN SUHU TUBUH BAYI BERAT LAHIR RENDAH DI NICU RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2018 - Ika Nur Sapurtri; Dwi Handayani; Maharani Nazmi Nasution (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Babies with low birth weight have a temperature that is unstable and prone to hypothermia (temperature <36,5ºC). Cold stress can increase mortality and hamper growth. The warmth of the mother's body or a known method of kangaroo care proved to be an effective heat source for infants born at term or low birth weight. This study aims to determine whether there is influence kangaroo care method to your body temperature low birth weight infants. This type of research is pre experiment with models (one group pre-post test design). The population of this research is all low birth weight babies. Sampling techniques in use purposive sampling, that the sampling technique was based on sample criteria specified by the researchers themselves. In this case the samples found as many as 22 people. Data analysis using paired sample t-test with a level of 95%. The results of this study gained an average prior to 34.7 kangaroo care method, after doing kangaroo care method 36.9. The mean before and after kangaroo care method 2.2273. Based on the analysis results showed pvalue (0.004) <α (0.05), It can be concluded no treatment effect kangaroo method to your body temperature low birth weight infants. Recommendations from this research is the kangaroo care method can be used as one LBW care that can be done by the mothers in raising and maintaining body temperature.